PERANAN LEMBAGA BANTUAN HUKUM DALAM MEMBERIKAN BANTUAN KEPADA MASYARAKAT DI BIDANG PERDATA (STUDI DI LBH MEDAN DAN LBH TRISILA SUMATERA UTARA) - RAMSES HARRY DOAN S (University of North Sumatera, 2013)
Justice is basically everyone’s expectations. Justice also affects each individual order. However,in some aspects of the law there are things that are not fair because the citizens are not equal before the law. In this case, the injustice occurs in the right of every citizen to obtain legal assitance. Therefore, Legal Aid as a Advocate has a strategic role in providing legal aid. And that will be disscussed here is the overview of the Law on Legal Aid, the history and development on the Legal Aid Society, and the function and role of these institutions. Keywords: Legal Aid Society, Legal Aid, Advocate, Civil.